2016
DOI: 10.3389/fpls.2016.00602
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Abscisic Acid on Ripening and Quality in Sweet Cherries: Differential Effects during Pre- and Post-harvest

Abstract: Sweet cherry, a non-climacteric fruit, is usually cold-stored during post-harvest to prevent over-ripening. The aim of the study was to evaluate the role of abscisic acid (ABA) on fruit growth and ripening of this fruit, considering as well its putative implication in over-ripening and effects on quality. We measured the endogenous concentrations of ABA during the ripening of sweet cherries (Prunus avium L. var. Prime Giant) collected from orchard trees and in cherries exposed to 4°C and 23°C during 10 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…The raw spectra for all 'Lapins' cherries sampled at the three temperatures, comprising the entire "training set", are shown in Fig. 1, from which it is clearly evident that the differences in spectra between individual samples in the VIS wavelength range (499-733 nm) were quite random and variable, likely because that band range contains absorption bands for chlorophylls and anthocyanins, both of which change significantly in concentrations as sweet cherry fruit ripens (Tijero et al 2016). The absorption bands in the NIR range were more regular and much less variable.…”
Section: Resultsmentioning
confidence: 99%
“…The raw spectra for all 'Lapins' cherries sampled at the three temperatures, comprising the entire "training set", are shown in Fig. 1, from which it is clearly evident that the differences in spectra between individual samples in the VIS wavelength range (499-733 nm) were quite random and variable, likely because that band range contains absorption bands for chlorophylls and anthocyanins, both of which change significantly in concentrations as sweet cherry fruit ripens (Tijero et al 2016). The absorption bands in the NIR range were more regular and much less variable.…”
Section: Resultsmentioning
confidence: 99%
“…Among these hormones, abscisic acid (ABA) and jasmonic acid seem to be involved in growth and ripening of sweet cherry fruits, which are non-climacteric. Various authors have reported that ABA promotes ripening in other non-climacteric fruits such as grapes, strawberries, and oranges, modulating anthocyanin biosynthesis and sugar accumulation (Kumar et al, 2014;Tijero et al, 2016). In sweet cherry fruit ABA levels have been shown to be high at the beginning of the first phase of growth, gradually decreasing during pit hardening, and increasing again during the final stage of fruit expansion (Ren et al, 2011;Luo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous ABA treatment can significantly increase the content of endogenous ABA in fruits and induce the upregulation of genes related to the anthocyanin-phenylpropane metabolic pathway and flavonoid pathway (Deluc et al, 2008;Gagné et al, 2011;Enoki et al, 2017). Exogenous ABA can promote the biosynthesis of anthocyanins in sweet cherry (Tijero et al, 2016), strawberry (Li et al, 2014;Li et al, 2015), grape (Hara et al, 2004;Koyama et al, 2014), and litchi (Wang et al, 2007;Hu et al, 2017) and can regulate the composition and content of pigments during the fruit-ripening period (Jiang and Joyce, 2003;Hara et al, 2004;Singh et al, 2014). In this study, 2 years of experiments showed that the ABA synthesis and receptor-related gene expression in the peel and flesh could be increased by exogenous ABA treatment, and the endogenous ABA content in the peel and flesh increased with the increase in the exogenous ABA concentration.…”
Section: Effects Of Exogenous Aba On the Synthesis Of Endogenous Aba mentioning
confidence: 99%